Answer:
(6,3)
Step-by-step explanation:
y=2/3 x - 1
y=-1/2 x + 6
Since both equations are equal to y, we can set them equal
2/3 x - 1 =-1/2 x + 6
We have fractions, so I will multiply by 6 to clear the fractions
6(2/3 x - 1) =(-1/2 x + 6)6
Distribute
4x -6 = -3x +36
Add 3x to each side
4x+3x -6 = -3x+3x +36
7x -6 = 36
Add 6 to each side
7x-6+6 = 36+6
7x = 42
Divide each side by 7
7x/7 = 42/7
x =6
Now we need to find y
y =2/3x -1
y = 2/3(6) -1
y = 4-1
y=3
(6,3)
-4(x + 1) + 5 = 17
Distribute -4 inside the parentheses.
(-4x - 4) + 5 = 17
Combine like terms (-4 + 5).
-4x + 1 = 17
Subtract 1 from both sides.
-4x = 16
Divide both sides by -4.
x = -4
Answer:
44 in.
Step-by-step explanation:
pi = 3.14 (in our case)
circumference = diameter x pi
circ. = 14 x 3.14, which equals to 43.96
round that and you get 44 in.
Answer:
Fraction 1/6. Decimal .6 or 1.6
Step-by-step explanation:
Answer:
780
Step-by-step explanation:
round up to the nearest ten